SPATIAL AND FUNCTIONAL RELATIONSHIP BETWEEN POLY(ADP-RIBOSE) POLYMERASE-1 AND POLY(ADP-RIBOSE) GLYCOHYDROLASE IN THE BRAIN - Poitras, Marc F. (2007)
Poly(ADP-ribose) polymerases (PARPs) are members of a family of enzymes that utilize NAD(+) as substrate to form large ADP-ribose polymers (PAR) in the nucleus. PAR has a very short half life due to its rapid degradation by poly(ADP-ribose) glycohydrolase (PARG). PARP-1 mediates acute neuronal cell death induced by a variety of insults including cerebral ischemia, MPTP-induced Parkinsonism, and CNS trauma. While PARP-1 is localized to the nucleus, PARG resides in both the nucleus and cytoplasm. Surprisingly, there appears to be only one gene encoding PARG activity, which has been characterized in vitro to generate different splice variants, in contrast to the growing family of PARPs. Little is known regarding the spatial and functional relationships of PARG and PARP-1. Here we evaluate PARG expression in the brain and its cellular and subcellular distribution in relation to PARP-1. Anti-PARG (α–PARG) antibodies raised in rabbits using a purified 30 kDa C-terminal fragment of murine PARG recognize a single band at 111 kDa in the brain. Western blot analysis also shows that PARG and PARP-1 are evenly distributed throughout the brain. Immunohistochemical studies using α-PARG antibodies reveal punctate cytosolic staining, whereas anti-PARP-1 (α–PARP-1) antibodies demonstrate nuclear staining. PARG is enriched in the mitochondrial fraction together with manganese superoxide dismutase (MnSOD) and cytochrome C (Cyt C) following whole brain subcellular fractionation and Western blot analysis. Confocal microscopy confirms the co-localization of PARG and Cyt C. Finally, PARG translocation to the nucleus is triggered by NMDA-induced PARP-1 activation. Therefore, the subcellular segregation of PARG in the mitochondria and PARP-1 in the nucleus suggests that PARG translocation is necessary for their functional interaction. This translocation is PARP-1 dependent, further demonstrating a functional interaction of PARP-1 and PARG in the brain.